2016
DOI: 10.1016/j.jana.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of HIV Status to Health Care Providers in the Netherlands: A Qualitative Study

Abstract: We qualitatively investigated perspectives on HIV disclosure to health care providers (HCP) by people living with HIV (PLWH). Perspectives varied across PLWH and between PLWH and HCP. Some PLWH felt they should always disclose so that HCP could take necessary precautions or because disclosure optimized care. Others felt that disclosure was not an obligation but a courtesy. Still others felt that disclosure was unnecessary as all HCP should apply universal precautions or because HIV status was not relevant to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Qualitative research from the United States showed that almost all participants agreed that they should disclose their HIV status to health care providers in any case and that few participants reported it was not necessary to disclose if the care was unrelated to their HIV diagnosis (Bairan et al, 2007). In research on disclosure of HIV status to health care providers in the Netherlands, some participants reported feeling that disclosure to health care providers was neither a necessity nor an obligation, but it was a courtesy (Stutterheim et al, 2016). For the most part, forum users in Russia do not discuss the possible harm to their own health in not telling doctors about their status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Qualitative research from the United States showed that almost all participants agreed that they should disclose their HIV status to health care providers in any case and that few participants reported it was not necessary to disclose if the care was unrelated to their HIV diagnosis (Bairan et al, 2007). In research on disclosure of HIV status to health care providers in the Netherlands, some participants reported feeling that disclosure to health care providers was neither a necessity nor an obligation, but it was a courtesy (Stutterheim et al, 2016). For the most part, forum users in Russia do not discuss the possible harm to their own health in not telling doctors about their status.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in contrast with research showing that concern for one’s health and quality treatment are the main reasons for disclosing status to health care providers. In research in the Netherlands, most participants reported being open with health care providers about their HIV status because they believed doctors needed to be informed to take the necessary medical precautions and also to ensure that they would receive quality health care services (Stutterheim et al, 2016). Research in the United Kingdom showed that PLHIV who disclose their status to dentists do so to reduce transmission risk or to prevent HIV-related oral disease (Edwards et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stigmatization in health care settings, in particular, has been found to be highly detrimental to the well-being of substance users with HIV [8,19]. In fact, anticipated or enacted stigmatizing reactions from health care professionals can inhibit both substance use dependence treatment and HIV care [8,20,21] through testing delays [22,23], treatment avoidance [19,24,25], late entry into care [24], non-disclosure of substance use and/or HIV status [19,21,26], and poor access to antiretroviral therapy [27], all of which also impede HIV prevention efforts [19,28]. It is therefore important to engage in efforts to reduce the stigmatization of substance users with HIV in health care settings, and to improve interactions between health care professionals and substance users with HIV.…”
Section: Introductionmentioning
confidence: 99%